ONLINE TRAINING IN THE WORKFORCE: A RECENT SYSTEMATIC REVIEW - Rahayu Ahmad-Don; Ahmad Suffian Mohd Zahari; Zalinawati Abdullah, (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
This systematic literature review explores the recent developments in online training within the workforce, highlighting its significance in fostering employee skills amid a digital transformation. Despite the increasing reliance on online training, organizations face persistent challenges, including engagement issues, varied digital literacy levels, and the effectiveness of training methods. To address these challenges, an extensive search of scholarly articles from reputable databases like Scopus and Web of Science was led, focusing exclusively on studies published in 2024, and following the PRISMA framework. The search yielded 27 articles deemed as final primary data, all of which were thoroughly analyzed. The findings were organized into three main themes: (1) Innovative Training Approaches and Technologies, (2) e-HRM Practices and Organizational Development, and (3) Online Training and Employee Well-being. The findings reveal that the use of the training strategies enhances the performance of the workers; 75% of the research revealed that satisfaction and retention levels rise. However, challenges such as adequate technical support and the need to develop content specific to the targeted learners’ needs continue to hinder the achievement of the best results in training. Thus, the effectiveness of online training as a tool for increasing the workforce’s capabilities is high; however, to implement the potential of this approach, it is necessary to solve the problems considered above. Subsequent studies should explore the long-term outcomes of online training and the new development of methodologies in order to gain more depth and insight into the area of organizational application.